FORMATION OF SKILLS IN JUNIOR SCHOOLCHILDREN SOLVE STEM MATHEMATICAL PROBLEMS - S.O. Skvortsova (Academy of Cognitive and Natural Sciences, 2004)
The problem of forming junior pupils' skills to do topic sums is considered in the article.